Production of specialty peppers under different protected agriculture systems - Collazo-Gámez, José Pablo; Robledo-Torres, Valentín; Mendoza-Villareal, Rosalinda; González-Cortes, Areli; Camposeco-Montejo, Neymar; Sandoval-Rangel, Alberto (Revista Mexicana de Ciencias Agrícolas, 2026)
Peppers are a species of great importance globally; due to their nutritional contribution, the demand for this product has increased, and as a result, lines called ‘specialties’ have now been created. Another effect of the demand for this product, together with the new challenges presented by climate change, is the increased use of protected agriculture in all its forms; this research aimed to evaluate the production of specialty peppers under different production systems. The work consisted of using various cultivars subjected to two production environments (greenhouse and shade net). Six cultivars were used and subjected to two production systems. In conclusion, it is mentioned that the Uanj111, Uanm74, and Uanj84 cultivars adapt very well to any production system without reducing their quality.
Keywords: Capsicum annuum L.; greenhouses; production